Elaboration and assessment of clinical protocols to support the evaluation of stand-to-sit activity - Maíra Junkes Cunha; Carolina Mendes do Carmo; Cássio Marinho Siqueira; Kelly Takara; Clarice Tanaka
Introduction Evaluation of sit-to-stand and stand-to-sit activities is used by physical therapists in patients with neurological and musculoskeletal disorders. Sit-to-stand activity presents different descriptions of phases and movements; however the phases of stand-to-sit activity have not been established yet.Objectives To describe the movements during stand-to-sit activity and create an evaluation protocol.Materials and methods Stand-to-sit activity was described on anterior and lateral views based on the observation of 27 healthy subjects. The body segments chosen to analyze were feet, ankles, knees, hips, pelvis, trunk, spine, upper limbs, head and cervical spine. The movements of body segments were described as adduction and abduction, eversion and inversion, valgus and varus, neutral position and asymmetry. The protocol was assessed with questionnaires answered by 12 physiotherapists experts in the area.Results Stand-to-sit activity was divided in 4 phases: 1- "Neutral position", 2- "Pre-squat", 3- "Squat" and 4- "Stabilization". Two models of protocols were developed considering 5 body segments to the anterior view and 7 segments for the lateral view.Conclusion Stand-to-sit activity was described in 4 phases with sequential movements of each body segment. These protocols allow physiotherapists to identify unusual movements of body segments during the stand-to-sit activity.